Kontribusi Dan Pengaruh Canva Terhadap Masa DepanProfesi Desainer Grafis - Lawrence Philip,B.A, M.M, Lawrence Philip,B.A, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
The Canva application has revolutionized the graphic design industry by making it a platform that is easily accessible to various groups, including graphic designers who have special expertise in this field. Canva offers multiple advanced features from templates, stock images, and collaboration tools with AI. It has more than 60 million users and produced over 7 billion designs. However, the success of this application has created challenges for professional graphic designers, due to a decrease in interest and demand for services by professional graphic designers themselves. This research aims to understand Canva's impact on the value and demand for professional graphic designer services and identify adaptation strategies that designers can use. The method used is data analysis and literature review regarding the influence of Canva in the creative industry. The research results show that although Canva can reduce demand for simple and non-complex design services, it can actually open up opportunities for designers to focus on more complex and creative projects. Adaptation strategies that can be implemented are using Canva as a supporting tool, improving skills and in-depth knowledge about design and management, and focusing on projects that require high expertise and creativity. This way, designers can remain relevant and competitive in this digital era. Adaptation and innovation are the keys for professional graphic designers in facing the changes brought by platforms like Canva.